Combined radiotherapy and immune checkpoint inhibition for the treatment of advanced hepatocellular carcinoma - Shannon, Alexander H.; Manne, Ashish; Diaz Pardo, Dayssy A.; Pawlik, Timothy M. (Frontiers in Oncology, 2023)
Hepatocellular Carcinoma (HCC) is one of the most common cancers and a leading cause of cancer related death worldwide. Until recently, systemic therapy for advanced HCC, defined as Barcelona Clinic Liver Cancer (BCLC) stage B or C, was limited and ineffective in terms of long-term survival. However, over the past decade, immune check point inhibitors (ICI) combinations have emerged as a potential therapeutic option for patients with nonresectable disease. ICI modulate the tumor microenvironment to prevent progression of the tumor.Radiotherapy is a crucial tool in treating unresectable HCC and may enhance the efficacy of ICI by manipulating the tumor microenvironment and decreasing tumor resistance to certain therapies. We herein review developments in the field of ICI combined with radiotherapy for the treatment of HCC, as well as look at challenges associated with these treatment modalities, and review future directions of combination therapy.